2014
DOI: 10.3390/nu6093929
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Dietary Fat/Carbohydrate Ratio and Body Mass Index on Iron Deficiency Anemia among Taiwanese Women

Abstract: Whether being overweight or obese is associated with increased risk of iron deficiency anemia (IDA) remains controversial. We evaluated the dietary intakes and risk for IDA in relation to body mass index (BMI). One thousand two hundred and seventy-four females aged ≥19 years, enrolled in the third Nutrition and Health Survey in Taiwan (NAHSIT) 2005–2008, were selected. Half of the women were either overweight (24.0%) or obese (25.3%). The overall prevalence of anemia, iron deficiency and IDA among adult women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 31 publications
4
35
1
3
Order By: Relevance
“…What is notable in the current research is that consuming visible fat in the meat increased chances of ID by up to 11-fold. These results are consistent with those of Chang et al, 44 who also showed, in the univariate analysis they conducted for data from ≥19-year-old women participating in the third NAHSIT study, that dietary fat increased the risk of IDA in overweight/obese women by 10-fold (i.e., OR: 10.119, 95% CI: 1.267-80.79).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…What is notable in the current research is that consuming visible fat in the meat increased chances of ID by up to 11-fold. These results are consistent with those of Chang et al, 44 who also showed, in the univariate analysis they conducted for data from ≥19-year-old women participating in the third NAHSIT study, that dietary fat increased the risk of IDA in overweight/obese women by 10-fold (i.e., OR: 10.119, 95% CI: 1.267-80.79).…”
Section: Discussionsupporting
confidence: 91%
“…This could therefore explain the current findings that being overweight and obese appear to be protective against anemia, ID, and IDA in young adults. Similar findings were published by Chang et al, 44 who reported that BMI in ≥19-year-old women participating in the third Nutrition and Health Survey in Taiwan (NAHSIT) 2005-2008 had a protective effect against IDA. In fact, the authors also showed that the IDA-overweight relationship resulted in an OR of 0.365 (95% CI: 0.181-0.736) and the IDA-obese relationship resulted in an OR of 0.480 (95% CI: 0.259-0.891) compared with normal-weight peers.…”
Section: Discussionsupporting
confidence: 88%
“…After applying the inclusion and exclusion criteria, a total of 26 original studies were ultimately included in the meta‐analysis (Fig. ), including 21 cross‐sectional studies and 5 case–control studies ; no cohort studies were include in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies reported serum iron levels , 10 reported TS% , 15 reported serum ferritin and 4 reported sTfR . Fifteen studies evaluated the risk of developing ID among overweight/obese populations , and four studies evaluated the risk of developing IDA . Detailed information regarding the weight diagnoses and outcomes is summarized in Supporting Information http://onlinelibrary.wiley.com/doi/10.1111/obr.12323/suppinfo.…”
Section: Resultsmentioning
confidence: 99%
“…Anthropometric measurement studies have been widely conducted internationally (especially BMI) and show a significant Dita Maria Virginia and Fenty correlation between anthropometric measurements and risk of anemia (Chang et al, 2014;Hausman et al, 2011;Saxena et al, 2011). However, studies in Indonesia related to anthropometry and anemia have not been conducted.…”
Section: Introductionmentioning
confidence: 99%